THE ZAKAT EFFECT ON ECONOMIC GROWTH, UNEMPLOYMENT, AND POVERTY IN THE ISLAND OF JAVA: PANEL DATA ANALYSIS 2001-2012 - Athoillah, Mohamad Anton (Politeknik Negeri Bandung, 2018)
The background of this research is the phenomena of zakat and poverty which conduct in six provinces on the Island of Java during the period 2001-2012. In the region and the period, the data of zakat acquisition on the one side, tends to increase sharply. While the data of poor population on the other side, although decreasing, the numbers are still high, even during that period had experienced twice fluctuations. This research uses panel data analysis, with a fixed-effect approach and data used are secondary data. The results of this study explained through quantitative interpretation procedure, which is sourced from the regression coefficients, such as the calculation results of the estimation model built. From the recursive models built, by placing economic growth and unemployment variables as control variables, this research found that zakat has positively and significantly effect on economic growth; negatively but not significantly effect on unemployment; and negatively and significantly effect on poverty. The findings of this study concluded that zakat can be used as an instrument of poverty alleviation in six provinces on the Island of Java. This study also recommends an assessment of the discourse of distributing zakat funds to non-Muslims. With a number of classic references available, there are opportunities to reformulate the distribution of zakat funds obtained. As a nation state, it is hoped that Indonesia can be used as an example of how zakat funds can become an adhesive for the life of the nation and state in a pluralistic and pluralistic society.Â Keywords: Zakat, Economic Growth, Unemployment and Poverty.